A Comparison of Picture-based Narratives by Finnish, Italian and English-speaking Children. Issue 3 (2nd April 2020) - Mäkinen, Leena; Gabbatore, Ilaria; Loukusa, Soile; Kunnari, Sari; Schneider, Phyllis
ABSTRACT: Narratives have been extensively studied in recent decades, but studies investigating differences and similarities in the narrative features from a cross-cultural or cross-linguistic point of view are limited. This study investigated the narrative language of typically developing monolingual four- and eight-year-old Finnish, Italian and Canadian English-speaking children (N = 177). Children completed a picture-based story generation task (Edmonton Narrative Norms Instrument) and their narratives were analyzed for story grammar, mental state terms, and productivity (number of clauses and irrelevant clauses). Results showed that narrative language skills develop with age and the developmental trend across the three languages is largely similar. The only exception was seen with a total number of clauses, as the Italian children did not show development in this variable as they were already quite talkative at the age of four. When comparing the three languages, many commonalities were seen, but also some differences in the early phase of narrative language development were detected, as Italian children outperformed Finnish (total number of clauses) and Canadian children (story grammar). However, differences were no longer evident at the age of eight. Understanding of different narrative traits is important in order not to draw misleading conclusions about a child's narrative competence.